Attractive regions: for whom? And how does that matter? - Antonio Russo; Ian Smith (European Regional Science Association (ERSA), 2012)
This paper reflects on human mobility ranges and their regional impacts. We first introduce an interpretative framework that situates place populations within a continuum of transiences and intensities: according to this, short- and long-term mobilities, generally associated with a binary of work-related migration and tourism, can be revisioned as a spectrum of fluid situations by which the permanence of people into places results from an articulated range of factors of attraction or place characteristics, and dynamically modifies this context. Indeed we postulate that different attraction factors attract different flows that could be characterised in this way as "regional audiences"; the fact that the same factors could be attractive to different audiences means that regions have to "tune" to an accommodate different users and uses, and as foreseen by Martinotti (1992) in his "four populations" urbanisation model, the success in doing that is a fundamental aspect of sustainable development We then use results from the ESPON 2013 Program (ATTREG project) to classify regions according to the populations that they were able to attract in the 2001-2008 period, and reflect upon the complex process of embedding different "audiences" into places in terms of attraction strategies and issues of resiliency. Our findings challenge the conventional wisdom that migrants are attracted by economic buoyancy and tight labour markets for highly skilled workers, and cast an interesting light about the synergetic effects of different population groups. We show for instance that "tourist regions", or regions that are particularly endowed for (and have been able to) attracting short-term mobilities, have had a good score in attracting longer-term forms of mobility, but only until economic conditions were favourable and some upper threshold have been reached; whereas regions with lower attractiveness scores have been better able to face the direct effects of the global crisis.
Keywords: J61; R58; 330; Migration; attraction; territorial capital; tourism